1998
DOI: 10.1111/j.1600-0714.1998.tb02099.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphometric analysis of squames obtained from normal oral mucosa and lesions of oral leukoplakia and squamous cell carcinoma

Abstract: Ramaesh T, Mendis BRRN, Ratnatunga N, Thattil RQ: Cytomorphometric analysis of squames obtained from normal oral mucosa and lesions of oral leukoplakia and squamous cell carcinoma. J Oral Pathol Med 1998; 27: 83–6. © Munksgaard, 1998. Cell and nuclear diameters (CD and ND) were measured in squames obtained from normal buccal mucosa and lesions of oral leukoplakia and squamous carcinoma (SCC) also from buccal mucosa. The study groups consisted of Group 1: normal buccal mucosa (n= 40); Group 2: lesions with no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
62
2
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 15 publications
11
62
2
6
Order By: Relevance
“…Measurements of NA and CA have been used as important parameters for detecting alterations in the epithelial tissues [9][10][11][12][13][14] . In our study, two situations were present: i) a reduction in both NA and CA (region 1), and ii) a reduction only in the NA (region 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of NA and CA have been used as important parameters for detecting alterations in the epithelial tissues [9][10][11][12][13][14] . In our study, two situations were present: i) a reduction in both NA and CA (region 1), and ii) a reduction only in the NA (region 2).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the effect of different types of diseases and aggressive agents on oral mucosa, such as alcohol, and tobacco 10,12,[20][21][22][23][24][25] . However, studies reporting physical trauma associated to use of orthodontic appliances are still scarce 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Ramaesh et al, (1998) [2] evaluated that the mean CD and ND values in normal smears varies from 43.29 µ-59.18 µm and 7.00-9.2 µm respectively using calibrated eye piece for measurement. The values of CD in our study were slightly more.…”
Section: Discussionmentioning
confidence: 99%
“…Uma área nuclear reduzida e uma área citoplasmática aumentada são fortes indicadores precoces da transformação maligna 18 . A partir deste conhecimento, um grande número de estudos foi realizado usando esta técnica descrita para avaliar a influência de diversos fatores sistêmicos e externos sobre as áreas nuclear e citoplasmática e a relação núcleo/citoplasma 22 . Vários fatores de risco vêm sendo apontados com relação ao desenvolvimento do câncer bucal.…”
Section: áRea Média Do Citoplasma (Micra)unclassified
“…Entretanto, já é sabido que quantidades excessivas de espécies de nitrogênio reativo produzidas durante a inflamação crônica podem desempenhar um papel importante na carcinogênese devido a danos ao DNA 27 . Na Índia, o vício de mascar betel associado ou não com tabaco é capaz de gerar uma redução significativa na área do citoplasma e um aumento na área do núcleo de células da mucosa bucal 8,22 . O uso do betel é comum em países orientais e tem se mostrado capaz de provocar o câncer bucal.…”
Section: áRea Média Do Citoplasma (Micra)unclassified